2012
DOI: 10.1155/2012/481641
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A and Hypertension in a Multiethnic Sample of US Adults

Abstract: Background. Bisphenol A (BPA) is a common chemical used in the manufacture of polycarbonate plastics and epoxy resins, with >93% of US adults having detectable BPA levels in urine. Recent animal studies have suggested that BPA exposure may have a role in several mechanisms involved in the development of hypertension, including weight gain, insulin resistance, thyroid dysfunction, endothelial dysfunction, and oxidative stress. However, no previous human study has examined the association between markers of BPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
96
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 31 publications
6
96
0
2
Order By: Relevance
“…10,11 Hypertension is a risk factor of cardiovascular diseases, and the 20 mm Hg increase of systolic BP doubles the risk of cardiovascular disease. 32 In light of this, the 5 mm Hg increase observed in the present trial may cause a clinically significant increase of risk of cardiovascular disorders, such as heart diseases and peripheral arterial diseases, which were associated with increased BPA concentration in the previous epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Hypertension is a risk factor of cardiovascular diseases, and the 20 mm Hg increase of systolic BP doubles the risk of cardiovascular disease. 32 In light of this, the 5 mm Hg increase observed in the present trial may cause a clinically significant increase of risk of cardiovascular disorders, such as heart diseases and peripheral arterial diseases, which were associated with increased BPA concentration in the previous epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 A previous study that analyzed the National Health and Nutrition Examination Survey data set also reported that increased urinary BPA concentration was associated with hypertension. 11 Furthermore, other studies had reported that increased urinary BPA was associated with heart and peripheral artery diseases, of which hypertension and decreased HRV are important risk factors. 9,[12][13][14] Considering that most of the previous epidemiological studies examined the crosssectional associations between urinary BPA concentration and health outcomes, a randomized intervention trial can provide a higher level of evidence and may elucidate the health effect of BPA more clearly.…”
mentioning
confidence: 99%
“…Humans are mainly exposed to BPA through food ingestion (Yamada et al 2002 ), and increasing evidence supports its association with impairment of male reproductive function, as well as other health problems and diseases; such diseases include diabetes, obesity, cardiovascular diseases, and cancer (Li et al 2010aSalian et al 2011 ;Batista et al 2012 ;Shankar and Teppala 2012 ;Lee et al 2012 ;Wang et al 2012a ). BPA acts primarily by mimicking the effect of estrogen hormones, modifying DNA methylation, and modulating enzyme activities in utero and in vivo, resulting in metabolic diseases, spermatogenesis defects, and/or infertility in males.…”
Section: Introductionmentioning
confidence: 99%
“…In previous epidemiologic studies, BPA levels have been shown to be associated with insulin resistance [9], type 2 diabetes mellitus [4,10,11], obesity [13], metabolic syndrome [12] and hypertension [14,15]. All these factors have been implicated in the pathophysiology of atherosclerosis.…”
Section: Discussionmentioning
confidence: 95%
“…Exposure to BPA is associated with increased risk of insulin resistance [9], type 2 diabetes [4,10,11], metabolic syndrome [12] and obesity [13]. Additionally, higher urinary BPA was associated with changes in heart rate variability and higher blood pressure [14,15]. Several pieces of published data have established an association between BPA exposure and the risk of atherosclerosis or cardiovascular diseases in adults.…”
Section: Introductionmentioning
confidence: 99%